2020
DOI: 10.26873/svr-895-2019
|View full text |Cite
|
Sign up to set email alerts
|

Egg Weight Affects Hatching Results, Body Weight and Fear-Related Behavior in Japanese Quails

Abstract: This study was conducted to determine effect of egg weight on hatching results, chick performance and tonic immobility duration in Japanese Quails. Eggs were weighed individually and divided by weight into four groups: group 1 = 11.0 -11.9 g, group 2 = 12.0 -12.9 g, group 3 = 13.0 -13.9 g and group 4 = 14.0 -14.9 g. Egg weight loss during incubation and hatching parameters were recorded. Additionally, hatching weight and body weight were measured until 5 weeks and tonic immobility (TI) test was performed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…These results are in line with the research conducted by Ismoyowati et al [10], who observed that the correlation coefficient between egg weight and hatching weight was 0.723 [10]. This study also in harmony to the research conducted by Abo-Samaha & El-Kazaz [11], who reported that there was a highly significant correlation between egg weight and hatching weight of quails.…”
Section: Resultssupporting
confidence: 92%
“…These results are in line with the research conducted by Ismoyowati et al [10], who observed that the correlation coefficient between egg weight and hatching weight was 0.723 [10]. This study also in harmony to the research conducted by Abo-Samaha & El-Kazaz [11], who reported that there was a highly significant correlation between egg weight and hatching weight of quails.…”
Section: Resultssupporting
confidence: 92%